In Search of Universal Grammar : From Old Norse to Zoque - Lohndal, Terje; Faarlund, Jan Terje, 1943- (Linguistik Aktuell/Linguistics Today ;)
Over the past two decades, studies of the phylogenetic emergence of language have typically focused on grammatical characteristics, especially those that distinguish modern languages from animal communication. The relevant literature has thus left the reader with the impression that language is either exclusively or primarily mental; in the latter case, its physical features, phonetic or manual, would be epiphenomena that may be overlooked. I argue that language is natural collective technology that evolved primarily to facilitate efficient communication in populations whose social structures.